Combined cardiopulmonary test and exercise Doppler echocardiography in systemic sclerosis. (3rd October 2022) - Quevedo, N M; Simbine, R E B; Bellagamba, C C A; Torres, M
Abstract: Background: Cardiopulmonary exercise test (CPET) and exercise Doppler echocardiography (EDE) may be useful for the early detection of pulmonary hypertension in systemic sclerosis (SSc) Aim: To assess the feasibility of CPET and EDE in detecting early changes in gas exchange and/or pulmonary hemodynamics in SSc Methods: From 2016 to 2021, we evaluated 19 SSc patients (Group 1, age = 52.58±11.27, women 17 (89.5%)), and age 32.10±6.67, men 17 (89.4%) matched healthy controls (Group 2). Simultaneous CPET and EDE were performed. With CPET, we assessed peak oxygen uptake (VO2), peak respiratory quotient (RQ), respiratory equivalent ratio for carbonic gas (VE/VCO2), and maximal respiratory equivalent divided by maximal ventilatory ventilation (V̇E Max/VVM). With EDE, we assessed tricuspid regurgitant velocity (TRV) jet and pulmonary flow acceleration time (ACT) to derive systolic pulmonary arterial pressure (SPAP). Results: Exercise duration was similar in the 2 groups (Group 1 = 9.2±2.93 vs Group 2 = 10.14±1.78 minutes). Among CPET parameters, SSc patients showed lower peak VO2 (Group 1 = 1.23±0.55 vs Group 2 = 2.45±0.7, p<0.001), similar RQ (1.10±0.10 vs 1.17±0.09;. p=0.036), VE/VCO2 (Group 1 = 31.90±3.65 vs Group 2 = 23.79±2.64, p<0.001) and V̇E Max/VVM (Group 1 = 1.93±0.60 vs Group 2 = 1.76±0.36, p=NS). With EDE, feasibility at peak stress was low for TRV (Group 1 = 42% vs Group 2 = 58%, p=NS), moderate for ACT (Group 1 = 53% vs Group 2 = 78%, p=NS) and high when at least one was technically adequate (Group 1 = 73% vs Group 2 = 100%, p<0.001). Rest TRV (Group 1 = 2.48±0.14 vs Group 2 = 2.08±0.12 m/s, p=0.033) and ACT (Group 1 = 100.14±10.63 vs Group 2 = 108.86±6.38 ms, p=0.482) showed similar values in the 2 groups (será que ficou similar?). During stress, TRV increased more markedly in SSc (Group 1 = 3.33±0.32 vs Group 2 = 2.34±0.09 m/s, p=0.004) and ACT decreased (Group 1 = 81.9±6.54 vs 73.39±5.18 ms, p=0.304), with estimated peak SPAP higher in SSc (Group 1 = 53.34±7.88 vs Group 2 = 43.33±5.49, p<0.001): see figure. Conclusion: CPET and EDE offer complementary information on gas exchange and pulmonary hemodynamics in SSc and can detect early alterations missed by resting assessment. The success rate of EDE increases significantly with the combination of TRV and ACT. Funding Acknowledgement: Type of funding sources: None.